Perancangan Komik Edukasi “Si Manis Bengis” sebagai Media Visual Pencegahan Diabetes Melitus pada Anak Sekolah Dasar Berbasis Design Thinking - Muhammad Guntur; Sunardy Kasim; Ni Putu Sinta Dewi (Indonesian Journal of Innovation Multidisipliner Research, 2026)
Diabetes Mellitus is a chronic metabolic disease characterized by elevated blood glucose levels resulting from impaired insulin production or function. In recent years, the prevalence of Diabetes Mellitus has increasingly affected primary school children due to excessive sugar consumption, unhealthy eating habits, and low levels of physical activity. The lack of engaging and age-appropriate educational media has contributed to students' limited understanding of diabetes prevention and the importance of adopting healthy lifestyles from an early age. Therefore, this study aims to design an educational comic entitled Si Manis Bengis as a visual learning medium to improve children's knowledge of diabetes prevention and to evaluate its effectiveness among primary school students. This study employed a design research approach using the Design Thinking method, which consists of five stages: empathize, define, ideate, prototype, and test. Data were collected through observations, interviews, documentation, and questionnaires involving 97 students and 14 teachers at SDN 133 Cakranegara. The collected data were analyzed using descriptive qualitative methods supported by simple quantitative analysis. The findings reveal that 58.76% of students prefer comics as a learning medium, while 83.51% reported that illustrations help them understand educational content more effectively. The developed comic successfully communicates diabetes prevention messages, including the risks of excessive sugar consumption and the importance of maintaining healthy eating habits and regular physical activity. Testing results also demonstrate an improvement in students' understanding of diabetes prevention after reading the comic. These findings indicate that Si Manis Bengis is an effective visual learning medium and has the potential to support health education and diabetes prevention among primary school children.